TARIF VOLUME LOKAL POHON JATI (Tectona grandis) DI HUTAN KEMASYARAKATAN SEDYO RUKUN KABUPATEN GUNUNGKIDUL - Dhea P Wijaya; Rochmad Hidayat; Probo Santoso (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
The activity of Teak (Tectona grandis) forest management on HKm in Gunungkidul is one of the wood production sources. However, the wood volume estimator for production planning is unavailable yet. Therefore, it is necessary to prepare a wood volume estimator to facilitate production planning. The goal of this research is to create a regression equation for the relationship between circumference and volume and compiling the local volume rate (TVL) of Teak trees (Tectona grandis) in the Sedyo Rukun Community Forest (Hkm) area, Banyusoco Village, Playen, Gunungkidul, Special Region of Yogyakarta. The sampling technique that used was purposive sampling with the sample was in the form of felled trees volume. The volume of the tree was calculated by using the smalian’s formula. TVL was arranged in some stages, data normality test, regression equation model, and validation test. The selection of the best model is considering into the criteria value of (coefficient of determination) R², (standard error of estimation) Se, F test, chi-square (x²), SA, SR, bias, and RMSE. Based on the research results, the best regression model is the power model with the formula V = with the value of R ² is 0.865; SE 0,390; SA -2.97; SR 0.16%; Bias 1.76%; RMSE 2.68% and chi-square 3,03.